(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the methodological foundations for developing students’ creative competence in the process of chemistry education in general secondary schools. During the research, the pedagogical and psychological aspects of creative thinking were studied, and the possibilities of using innovative and interactive methods in teaching chemistry were highlighted. In addition, effective approaches aimed at developing students’ independent thinking, problem-solving skills, and creative approach were substantiated. The article presents the results obtained through theoretical analysis, pedagogical observation, experiment, questionnaire, and testing methods, and compares the effectiveness of lessons based on traditional and creative approaches. The research findings indicate that the use of creative methods significantly enhances students’ knowledge level, activity, and creative thinking. In conclusion, scientific and practical recommendations for developing creative competence in chemistry education have been developed, which contribute to improving the educational process.